2020
DOI: 10.1016/j.jaci.2020.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IP-10 and MCP-3 levels are highly associated with disease severity and predict the progression of COVID-19

Abstract: Background: The outbreak of coronavirus disease 2019 caused by the severe acute respiratory syndrome coronavirus 2 was first reported in Wuhan, December 2019, and continuously poses a serious threat to public health, highlighting the urgent need of identifying biomarkers for disease severity and progression. Objective: We sought to identify biomarkers for disease severity and progression of COVID-19. Methods: Forty-eight cytokines in the plasma samples from 50 COVID-19 cases including 11 critically ill, 25 se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
620
5
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 618 publications
(687 citation statements)
references
References 41 publications
50
620
5
12
Order By: Relevance
“…In addition, immature neutrophil numbers strongly correlated with IL-6 and IP-10. IL-6 and IP-10 are consistently upregulated during a cytokine storm and are associated with severe ARDS 9,10,31,32 . While some studies report inflammatory monocytes as the source of IL-6 9,33,34 , our results suggest that immature neutrophils could also be a non-negligible source of IL-6 during COVID-19-induced cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immature neutrophil numbers strongly correlated with IL-6 and IP-10. IL-6 and IP-10 are consistently upregulated during a cytokine storm and are associated with severe ARDS 9,10,31,32 . While some studies report inflammatory monocytes as the source of IL-6 9,33,34 , our results suggest that immature neutrophils could also be a non-negligible source of IL-6 during COVID-19-induced cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…Lopinavir/ Ritonavir and Remdesivir, showed that these drugs were not that effective as we had expected in Chinese patients with COVID-19 [4,5]. Because several in ammatory factors are observed dramatically increasing, overreactive immunopathological mechanisms are surmised to be responsible for multiple organ damage in COVID-19 [6]. Some researchers hypothesize that patients with COVID-19 might bene t from some antirheumatic drugs, such as hydroxychloroquine (HCQ)/ chloroquine (CQ) and tocilizumab (TCZ),for their effects on immune regulation and suppression [7].…”
Section: Introductionmentioning
confidence: 83%
“…The plasma of the children COVID-19 patients (N = 11) were collected at the earliest possible time-point after hospitalization. The concentrations of 48 cytokines and chemokines were measured using Bio-Plex Pro Human Cytokine Screening Panel (Bio-Rad) as previously reported together with plasma collected from 50 adult patients and 8 healthy control [17,18].…”
Section: Cytokine and Chemokine Measurementsmentioning
confidence: 99%
“…Recent studies have elucidated the viral shedding patterns of SARS-CoV-2 mainly based on adult patients [11][12][13][14]. Cytokine storm, which contributes to acute lung injury and development of acute respiratory distress syndrome (ARDS) [15], has been found during SARS-CoV-2 infection [16][17][18]. Meanwhile, several cytokines have been shown to closely associate with the diseases severity and outcome of COVID-19 in adults [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation